Role ofProphet Muhammad (SAWS) in Erosion of Slavery - T Alalwani, Dr.Ruqaia (IJRDO - Journal of Social Science and Humanities Research, 2017)
Prophet Muhammad (SAWS) played a vital role in erosion of slavery through the teachings of Islam. He emphasized that only Allah should be glorified and every living soul has duties upon him, fulfillment and breach of those duties are based on the free will of human beings. His message was a beacon of light in a society where people enter into a vicious cycle of slavery as war captives, debt defaulter or kidnapped and ultimately sold in slave markets. One can trace back the history of slavery as ancient as 5000 BC, however more appalling forms appear in fifteen to seventeenth century particularly in Europe and America. There are many sayings clarifying the strong stance of Prophet Muhammad (SAWS) against slavery. He was not only vocal about rights of slaves, but also encouraged to set them free. He treated them with humanity, love, and affection to set a practical example. He started an era where slaves were no more exploited and have the rights of free lodging and marriage; they became human beings and were judged only on the basis of their virtues.